One‐Pot Approach to Organo‐Phosphorus–Chalcogen Macrocycles Incorporating Double OP(S)SCn or OP(Se)SeCn Scaffolds: A Synthetic and Structural Study. Issue 23 (26th April 2016) - Hua, Guoxiong; Du, Junyi; Slawin, Alexandra M. Z.; Woollins, J. Derek
Abstract: The development of new methodology for the preparation of functional macrocycles with practical applications is an important research area in macromolecular science. In this study, we report a new one‐pot route for the synthesis of a series of macro‐heterocycles by incorporating two phosphorus atoms and two chalcogen atoms and two oxygen atoms (double OP(S)SC n or OP(Se)SeC n scaffolds). The three‐component condensation reactions of 2, 4‐diferrocenyl‐1, 3, 2, 4‐diathiadiphosphetane 2, 4‐disulfide (FcLR, a ferrocene analogue of Lawesson's reagent) or 2, 4‐bis(4‐methoxyphenyl)‐1, 3, 2, 4‐dithiadiphosphetane 2, 4‐disulfide (LR, Lawesson's reagent), or 2, 4‐diphenyl‐1, 3, 2, 4‐diselenadiphosphetane 2, 4‐diselenide (WR, Woollins' reagent), disodium alkenyl‐diols, and dihalogenated alkanes are performed, giving rise to soluble and air or moisture‐stable macrocycles in good‐to‐excellent yields (up to 92 %). This is the first systemically preparative and readily scalable example of one‐pot ring opening/ring extending reaction of three‐components to prepare phosphorus–chalcogen containing macrocycles. We also provide a systematic crystallographic study. Abstract : Easy accesses to macrocycles ! A variety of phosphorus–chalcogen macrocycles have been synthesised (see figure) readily by using a one‐pot three‐component condensation reaction of the four‐membered ring chalcogenation reagents, disodium alkenyl‐diols, and dibromoalkanes.